(untitled) (Edad Media. Revista de Historia, 2019)
This contribution concentrates its interest on the lowlands of the territory of Reggio Emilia between the eleventh and the thirteenth centuries. In particular, the focus is addressed to the difficult relationship between man, water and human development as related to the settlement network and the agricultural exploitation of the resources, by means of the collation of different sources of a geomorphological, written or archaeological nature.